2020
DOI: 10.26434/chemrxiv.12153021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Structural Mechanism of Glutathione as a Potential Peptide Inhibitor to the Main Protease (Mpro): CoviD-19 Treatment, Molecular Docking and SAR Study

Abstract: 2019-nCoV Coronavirus spread all over the world and obliged one billion people in open confinement, no treatments or vaccine have been yet found against this pandemic. The Main Protease (M<sup>pro</sup>) is an attractive drug target, because it is the essential protein for the virus invasion. This study aims to test in silico the effect of five vitamins and a natural antioxidant against M<sup>pro</sup>, using molecular docking study, with Autodock Vina and Discovery Studio visualizer so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Recently, it has also been found that GSH and its precursor's supplements aid in recovery from respiratory distress in patients infected with COVID-19 [48,49]. GSH has been identified as a source that can inhibit the main protease (Mpro) of COVID-19 [50]. In this context, the use of GSH as a supportive strategy for the treatment of COVID-19 infection can be recommended after a successful trial.…”
Section: Oxidative Stress Antioxidants and Neurotransmittersmentioning
confidence: 99%
“…Recently, it has also been found that GSH and its precursor's supplements aid in recovery from respiratory distress in patients infected with COVID-19 [48,49]. GSH has been identified as a source that can inhibit the main protease (Mpro) of COVID-19 [50]. In this context, the use of GSH as a supportive strategy for the treatment of COVID-19 infection can be recommended after a successful trial.…”
Section: Oxidative Stress Antioxidants and Neurotransmittersmentioning
confidence: 99%
“…Investigation demonstrates that selenium is significantly involved in reducing the body's free radicals with the participation of a group of vitamin E-related enzymes. A recent study by Linani et al reported that administrating glutathione accompanied vitamin E was effective in COVID-19 treatment [180]. In another randomized, low-population clinical trial (small pilot RCT), the positive effects of vitamin E in chronic hepatitis B treatment were investigated.…”
Section: Vitamin Ementioning
confidence: 99%